Foot-and-Mouth Disease Virus Capsid Protein VP1 Antagonizes TPL2-Mediated Activation of the IRF3/IFN-β Signaling Pathway to Facilitate the Virus Replication - Hao, Junhong; Shen, Chaochao; Wei, Nannan; Yan, Minghao; Zhang, Xuegang; Xu, Guowei; Zhang, Dajun; Hou, Jing; Cao, Weijun; Jin, Ye; Zhang, Keshan; Zheng, Haixue; et al. (Frontiers in Immunology, 2021)
Foot-and-mouth disease (FMD) is a severe, highly contagious viral disease of cloven-hoofed animals. In order to establish an infection, the FMD virus (FMDV) needs to counteract host antiviral responses. Tumor progression locus 2 (TPL2), a mitogen-activated protein kinase, can regulate innate and adaptive immunity; however, its exact mechanisms underlying TPL2-mediated regulation of the pathogenesis of FMDV infection remain unknown. In this study, we confirmed that TPL2 could inhibit FMDV replication in vitro and in vivo. The virus replication increased in Tpl2-deficient suckling mice in association with reduced expression of interferon-stimulated genes interferon-α (IFN-α) and myxovirus resistance (MX2) and significantly reduced expression of C-X-C motif chemokine ligand 10 (CXCL10), interferon regulatory factor 3 (IRF3), and IRF7, while the phosphorylation of IRF3 was not detected. Moreover, the interactions between TPL2 and VP1 were also confirmed. The overexpression of TPL2 promoted IRF3-mediated dose-dependent activation of the IFN-β signaling pathway in association with interactions between IRF3 and TPL2. VP1 also inhibited phosphorylation of TPL2 at Thr290, while Thr290 resulted as the key functional site associated with the TPL2-mediated antiviral response. Taken together, this study indicated that FMDV capsid protein VP1 antagonizes TPL2-mediated activation of the IRF3/IFN-β signaling pathway for immune escape and facilitated virus replication.